Icy, Watery, Liquescent: Sensing and Feeling Climate Change on Northwest Greenland’s Coast - Nuttall, Mark (Journal of Northern Studies, 2020)
In the coastal areas of Northwest Greenland, water, ice and land intermingle with the lives and trajectories of humans and animals, take on a multitude of shapes and forms, and give rise to a complexity of social relations. However, as in other parts of the Arctic, the effects of climate change are increasingly evident. Sea ice cover during winter and spring is less extensive than people living in the region today have known it to be, while icebergs calve from tidewater glaciers at arate faster than they and scientists have previously observed. Glacial ice mass is diminishing and increased meltwater runoff from glacial fronts affects water temperature, ocean depths and circulation patterns, as well as the formation and thickness of sea ice and the movements of marine mammals and fish. These changes have profound implications for local livelihoods and mobilities, the wider regional economy, and human-animal interactions. In this article, I consider what some of the effects of climate change mean for people and their surroundings in Northwest Greenland’s Upernavik area and draw attention to liquescence as a counter to the “ice is melting” narrative that typically understands climate change as liquification. While the scientific monitoring of sea ice, glacial ice loss, and surface melt on the inland ice in the Upernavik region—and in the wider Northwest Greenland area—is well established, and contributes to the regular updating of state of the ice reports for the Arctic, little attention has been given to what these changes to ice and water mean for people and for human and non-human relational ontologies. Thinking of this in terms of liquescence, rather than liquification is a way of moving toward a deeper appreciation of people’s experiences and sense-making of the changes happening to them and to their surroundings as affective, sensorial and embodied.